Metabolic (cytoprotective) therapy of menopausal disturbances - S. N. Tolstov; V. B. Mychka (Кардиоваскулярная терапия и профилактика)
The paper presents modern views on cardiovascular aspects of menopause and metabolic therapy of menopausal disturbances with meldonium (Mildronate®). The role of estrogen deficiency in climacteric disturbance development, key pathogenetic mechanisms of menopausal metabolic syndrome (MS), and relevant features of arterial hypertension and endothelial dysfunction development are discussed. The data on Mildronate® clinical use for cardiovascular prevention are summarized. The wide prevalence and multiple clinical manifestations of menopausal disturbances point to the need for their complex therapy. Mildronate® therapy is a new approach for systemic correction of metabolic disturbances in women with climacteric symptoms and menopausal MS.